The Effect of Environmental Uncertainty and Financial Distress on Tax Avoidance with Business Strategy as a Moderating Variable: Case Study of Manufacturing Companies in 2021 to 2023 - Abdillah Akhsan; Eva Wany; Sarah Yuliarini (Economic Reviews Journal, 2026)
This study aims to analyze the influence of financial distress and environmental uncertainty on tax avoidance. As well as analyzing the moderation effect of business strategies on the influence of financial distress and environmental uncertainty on tax avoidance. This study includes quantitative research, the population is a manufacturing company in IDX in 2021 – 2023, the determination of samples uses purposive sampling. The sample is 81 companies. Using secondary data. Data analysis uses Moderated Regression Analysis (MRA). The results of the study concluded that financial distress had a significant effect on tax avoidance in manufacturing companies in 2021 – 2023. However, environmental uncertainty has no effect on tax avoidance in manufacturing companies in 2021 – 2023 while business strategy moderates the influence of environmental uncertainty and financial distress on tax avoidance in manufacturing companies in 2021 – 2023.